2014
DOI: 10.1186/preaccept-2533843621365334
|View full text |Cite
|
Sign up to set email alerts
|

Defense suppression benefits herbivores that have a monopoly on their feeding site but can backfire within natural communities

Abstract: BackgroundPlants have inducible defenses to combat attacking organisms. Hence, some herbivores have adapted to suppress these defenses. Suppression of plant defenses has been shown to benefit herbivores by boosting their growth and reproductive performance.ResultsWe observed in field-grown tomatoes that spider mites (Tetranychus urticae) establish larger colonies on plants already infested with the tomato russet mite (Aculops lycopersici). Using laboratory assays, we observed that spider mites have a much high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
93
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(104 citation statements)
references
References 33 publications
10
93
1
Order By: Relevance
“…Previously, we showed that mixing T. urticae and T. evansi from the start on the same leaf results in intermediate suppression of defenses (Alba et al, 2015). In nature, however, mites usually infest plants sequentially (Ferragut et al, 2013;Glas et al, 2014). Therefore, here we first allowed T. evansi to establish its feeding site and introduced T. urticae to the adjacent leaf tissue 2 d later, and vice versa.…”
Section: Introductionmentioning
confidence: 95%
“…Previously, we showed that mixing T. urticae and T. evansi from the start on the same leaf results in intermediate suppression of defenses (Alba et al, 2015). In nature, however, mites usually infest plants sequentially (Ferragut et al, 2013;Glas et al, 2014). Therefore, here we first allowed T. evansi to establish its feeding site and introduced T. urticae to the adjacent leaf tissue 2 d later, and vice versa.…”
Section: Introductionmentioning
confidence: 95%
“…Odor cues emanating from infested plants were suggested to affect thrips choice, but no further studies on the mechanisms operating in these plant–thrips interactions have been described. Some studies have demonstrated that activation of plant defenses by other arthropod herbivores can affect thrips preference and survival (Delphia et al 2007), highlighting the central role of induced defenses in shaping the community of herbivores (Poelman et al 2008, Erb et al 2011, Glas et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Antagonistic interactions between these pathways are well documented (Pieterse et al 2012). And a previous study attributed the observed enhancement of T. urticae performance in the presence of russet mites (Aculops lycopersici) to the attenuation of JA-defences because of JA-SA antagonism (Glass et al 2014)although Nachappa et al (2013) also reported positive effects of Tomato spotted wilt virus on T. urticae fecundity that did not appear to involve SA-JA crosstalk. In the current study, TYLCV and B. tabaci elicited significantly higher levels of SA and its associated marker gene (PR-1a) in combination than either induced in isolation (Figs 2c & 3d), and these levels were thus consistently higher in plants where T. urticae co-occurred with B. tabaci and TYLCV than in plants on which it co-occurred with either of these competitors separately (Figs 2c & 3d).…”
Section: Discussionmentioning
confidence: 94%
“…Total RNA was extracted and purified, and cDNA was synthesized as described by Su et al (2015a). To test the hypothesis that TYLCV infection suppresses T. urticae-induced JA-defences in B. tabaci-infested tomato, we measured defence responses in leaflets from T. urticae-infested and B. tabaci-infested plants by quantifying transcript levels of TYLCV influences plant-herbivore interactions 599 well-established JA-related and SA-related defence marker genes that are strongly induced by T. urticae feeding on tomato (Glass et al 2014;Alba et al 2015). Polyphenol oxidase-F (PPO-F), jasmonate-inducible protein 21 (JIP-21) and wound-induced proteinase inhibitor II (WIPI-II) were selected as JA-marker genes, while pathogenesis-related protein 1a (PR-1a) was selected as an SA-marker gene.…”
Section: Quantification Of Gene Expression By Qrt-pcrmentioning
confidence: 99%
See 1 more Smart Citation